Ten-Year Trends in the Use of Oral Anticoagulants in Australian General Practice Patients With Atrial Fibrillation - Bezabhe, Woldesellassie M.; Bereznicki, Luke R.; Radford, Jan; Wimmer, Barbara C.; Curtain, Colin; Salahudeen, Mohammed S.; Peterson, Gregory M. (Frontiers in Pharmacology, 2021)
Objective Appropriate use of oral anticoagulants (OACs) reduces the risk of stroke in patients with atrial fibrillation (AF). The study characterised the prescribing of OACs in people with AF in the Australian primary care setting over 10 years. Design Retrospective population study. Setting and Participants We performed 10 sequential cross-sectional analyses of patients with a recorded diagnosis of AF between 2009 and 2018 using national general practice data. The proportion of patients with AF who were prescribed an OAC based on their stroke risk was examined. Primary and secondary outcomes The primary outcome was the proportion of high stroke risk patients who were prescribed an OAC over a decade. The secondary outcome was variation in OAC prescribing among general practices. Results The sample size of patients with AF ranged from 9,874 in 2009 to 41,751 in 2018. The proportion who were prescribed an OAC increased from 39.5% (95% CI 38.6%-40.5%) in 2009 to 52.0% (95% CI 51.5%-52.4%) in 2018 (p for trend <0.001). During this time, the proportion of patients with AF and high stroke risk who were prescribed an OAC rose from 41.7% (95% CI 40.7%-42.8%) to 55.2% (95% CI 54.7%-55.8%; p for trend <0.001) with the direct-acting oral anticoagulants accounting for over three-quarters of usage by 2018. There was substantial variation in OAC prescribing between general practices. In 2018, the proportion of moderate to high stroke risk patients who were prescribed an OAC was 38.6% (95% CI 37.2%-40.1%) in the lowest practice site quintiles and 65.6% (95% CI 64.5%-66.7%) in the highest practice site quintiles. Conclusions Over the 10 years, OAC prescribing in high stroke risk patients with AF increased by one-third. There was considerable variation in OAC prescribing between general practices.